BIBLIOTECA – O LUME DESCHISĂ PENTRU TOȚI - JAVELEA, șef, Serviciul programe, activități cu publicul, Departamentul dezvoltare și comunicare, Svetlana (BIBLIOPOLIS, 2020)
Open Door Week is a program of collections, library services and offers promotion. During the week the libraries are establishing partnerships; confirming the status of cultural centre for the community; attracting a greater number of new users; enhancing the library image in the community.